Pengolahan cengpo ‘Kemoceng Kelopo’ untuk menunjang perekonomian masyarakat Desa Ploso Kecamatan Tegalombo Kabupaten Pacitan - Winarsih, Sulis Setiani, Mufida Windy Istiani (Universitas PGRI Madiun, 2017)
Ploso Village is one of 11 villages in Tegalombo sub-district, Pacitan regency, which is 23 km to the north from the district center and has an area of 701.49 hectares. The majority of the villagers work as farmers with coconut as the main commodity. The author took the initiative to introduce a product derived from the waste of coconut fibers considering the use of coconut trees only on the fruit, shell and tree alone. This product is named